Análisis del control interno de los propiedad, planta y equipo en el Cuerpo de Bomberos del Cantón Caluma periodo 2019 - Correa Tipán, Jasmin Lisseth (2020)
The Caluma Canton Fire Department located in the Los Rosales neighborhood and founded on September 4, 1980, is a non-profit entity with legal status stipulated in Ministerial Agreement No. 1313, always at the service of emergencies and support to those most need it. Internal Control is an essential tool to support managers within the entity, to achieve reasonable security by complying with current regulations and laws that guarantee credibility when requesting any information on Property, Plant and Equipment of the Fire Department. The focus on the audit and control research line allowed the analysis of the process of the assets owned by the entity. This case study on the Analysis of the Internal Control of Property, Plant and Equipment in the Fire Department of the Canton Caluma period 2019, led to find through the survey and observation technique the shortcomings in the warehouse department such as the lack of organization and coding, non-existence of physical findings and due detailed information on each of the goods that the warehouse keeper guards, all this was generated because the warehouse staff carried out their activities empirically, requiring relevant training on the registration process of assets and that is carried out through the SIG-AME Comprehensive Management System, considered one of the fundamental systems to maintain an ideal control aimed at facilitating the management tasks that the custodian has, in addition to allowing to obtain truthful information efficiently and effective in the operations to be carried out within the entity and when issuing reports.